2017
DOI: 10.1182/bloodadvances.2017009209
|View full text |Cite
|
Sign up to set email alerts
|

The impact of von Willebrand factor on factor VIII memory immune responses

Abstract: Immune tolerance induction (ITI) with aggressive infusion of factor VIII (FVIII) is the current strategy used to eradicate FVIII inhibitors and restore normal FVIII pharmacokinetics in inhibitor patients. Whether the use of FVIII products containing von Willebrand factor (VWF) will affect the efficacy of ITI is still controversial. In this study, we explored the impact of VWF on FVIII memory immune responses in hemophilia A (HA) mice. A T-cell proliferation assay and cytokine profile analysis were used to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Chen et al reported that VWF could attenuate FVIII-primed CD4 T cell proliferation in response to rhFVIII restimulation. Their studies showed that VWF could mitigate FVIII-specific memory B cell maturation and anti-FVIII antibody production both ex vivo in a memory B cell-based ELISPOT assay and in vivo in an immunocompromised FVIII deficient animal model upon rhFVIII restimulation (37). Results from this study support the notion that FVIII stored together with VWF in platelets may be less immunogenic compared to plasma FVIII in a milieu of preexisting anti-FVIII immunity.…”
Section: The Presence Of Protective Protein Vwf To Fviii In Plateletssupporting
confidence: 63%
“…Chen et al reported that VWF could attenuate FVIII-primed CD4 T cell proliferation in response to rhFVIII restimulation. Their studies showed that VWF could mitigate FVIII-specific memory B cell maturation and anti-FVIII antibody production both ex vivo in a memory B cell-based ELISPOT assay and in vivo in an immunocompromised FVIII deficient animal model upon rhFVIII restimulation (37). Results from this study support the notion that FVIII stored together with VWF in platelets may be less immunogenic compared to plasma FVIII in a milieu of preexisting anti-FVIII immunity.…”
Section: The Presence Of Protective Protein Vwf To Fviii In Plateletssupporting
confidence: 63%
“…VWF, the binding partner for FVIII, protect FVIII from protease degradation in the circulation as a protector protein for FVIII. [ 22 ] The low level or nonfunctional of VWF could lead to the FVIII activity decrease. All PK parameters had a correlation with VWF:Ag in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The titers of anti-FVIII inhibitors were determined by a modified Bethesda assay, as described in our previous reports. 31,32 C57BL/6J WT and mixed bone marrow (BM) chimeric mice, which had normal levels of endogenous murine FVIII, were immunized with recombinant human full-length FVIII (rhfF8, Kogenate FS; Bayer Pharma, Whippany, NJ) at a dose of 200 U/kg weekly for 4 weeks. One week after the last immunization, blood samples were collected for assays.…”
Section: Methodsmentioning
confidence: 99%